Changes in the somatic build and physical fitness of physical education students in the years 2004 and 2014 - Wasiluk, Agnieszka; Saczuk, Jerzy (Akademia Wychowania Fizycznego w Poznaniu)
Introduction. In the current situation of the demographic lowand strong competition on the educational market, such issues asthe level of education as well as competences and predispositionsof students are under discussion more and more frequently. Aimof Study. The aim of this study was to analyse differences in bodybuild and physical fitness of physical education (PE) studentsin the years 2004 and 2014. Material and Methods. In 2004 theauthors examined 112 females and 287 males who were second-yearstudents. The tests were repeated in 2014 and included 98 femalesand 242 males. Anthropometric features were measured accordingto Martin and Saller guidelines, and these measurements, in turn,were used to calculate body build type according to Heath–Cartermethod. Physical fitness was assessed with the use of Eurofit test.Results. In the assessed decade only slight changes in basic somaticfeatures and negative changes in body build (especially in men)were noted. Physical fitness of students was similar to the resultsobtained 10 years earlier. Conclusions. The observed secular trendsin body build and physical fitness may be interpreted as the effectsof the improvement of living conditions of the male subjects andthe improvement of admission process at the university.
Keywords: secular trend; Heath–Carter method; somatotype; EUROFIT